Investigation on Loss of Tail-rotor Effectiveness of helicopter with ducted fan tail rotor - Roh, N.; Park, D.; Oh, S. (My University, 2018)
The loss of tail rotor effectiveness (LTE) means steep loss of yawing stability in particular flight condition due to the reduction of tail rotor performance. In this study, numerical analysis is conducted to investigate the LTE characteristics of the ducted fan tail rotor. The complete helicopter configuration (main rotor, ducted fan tail rotor, fuselage, and empennage) is simulated to obtain the mechanism of wake interaction for a range of whole crosswind angle, from 0?? to 360??. It is confirmed that both the main rotor wake and port wing wake are immersed within tail rotor disk by the suction force of tail rotor. The main rotor wake rotates in the opposite direction to the tail rotor, and it contributes to the improvement of thrust. The port wing wake works oppositely. As the flow entered from the front side, both magnitude and vibration of thrust are increased due to the broad influence of the main rotor wake. Nevertheless, direct impingement of wakes is prohibited by the structures of tail rotor system, and also substantial wake of tail rotor prevents re-entering of tip vortex. Consequently, the ducted fan tail rotor maintains acceptable thrust variation in comparison with the open type tail rotor.